"Bridging the Gap between Food Pantries and the Kitchen Table": Teaching Embodied Literacy in the Technical Communication Classroom. Issue 3 (3rd July 2018) - Swacha, Kathryn Yankura
ABSTRACT: Drawing from literature on communication as a physical, material experience, this article expands Cargile Cook's "layered literacies" (2002) pedagogical framework to include a seventh literacy—embodied literacy. The article uses a classroom case study in which students coproduced a cookbook with low-income, elderly, disabled users, to demonstrate how students can become more responsible and effective technical communicators by recognizing users' divergent embodied experiences. The article includes suggestions for concrete classroom practices that encourage such embodied literacy.